Analisis Pengaruh Variabel Individual dan Kontekstual terhadap Status Pengangguran pada Angkatan Kerja Usia Muda Lulusan SMK di Provinsi Jawa Tengah Tahun 2023 - Amelia, Izumi Citra; Muchlisoh, Siti (Seminar Nasional Official Statistics, 2025)
Efforts to increase employment opportunities can be done through vocational education, namely SMK. Central Java is a province that has adequate carrying capacity to organize vocational education. However, in reality, the TPT of SMK graduates in Central Java is still high and has increased. The TPT is dominated by the labor force aged 15-24 years. This can lead to socioeconomic problems. Therefore, this study was conducted to determine the variables that affect the unemployment status of young vocational graduates in Central Java Province in 2023. This study uses Sakernas raw data for August 2023, BPS publications. This research was analyzed descriptively and inferentially using multilevel binary logistic regression. Based on the research results, the variables that have a significant effect on unemployment status at the individual level are gender, marital status, field of expertise, and year of graduation. Then at the district/city level, the variables include HDI and GRDP. Meanwhile, the pre-employment program participation variable has no significant effect on unemployment status.